William P. Cochran correspondence - Cochran, William P.
ALS (1832 July 4-5; Faial Island, Azores) from Cochran to his father, Joseph Cochran, of New Boston, N.H., regarding his life as an inexperienced whaler. Mentions his seasickness, whales caught, fresh produce supplies for the ship, and sailing for the Cape Verde Islands. Whaleship is unnamed but is possibly the Grand Turk, Abraham T. Eddy, master, which sailed from New Bedford, Mass., for the South Atlantic on June 2, 1832.
Whaler.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cochran, Joseph, -- active 1832 -- Correspondence; Eddy, Abraham T; Grand Turk (Whaling ship); Motion sickness; Whaling -- Atlantic Ocean; Whaling -- Massachusetts -- New Bedford; Cape Verde -- Description and travel; Faial Island (Azores) -- Description and travel; Whalers (Persons)